2007
DOI: 10.1099/jmm.0.47027-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of species of Abiotrophia, Enterococcus, Granulicatella and Streptococcus by sequence analysis of the ribosomal 16S–23S intergenic spacer region

Abstract: The feasibility of sequence analysis of the ribosomal 16S-23S intergenic spacer region (ITS) was evaluated for identification of 24 species of Streptococcus, one species of Abiotrophia, 18 species of Enterococcus and three species of Granulicatella. As GenBank currently lacks ITS sequence entries for many species of these four genera, the ITS sequences of 38 type strains were first sequenced and submitted to GenBank to facilitate species identification of these genera. Subsequently, the ITS sequences of 217 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…By the current and published standard, our unusual sequence variants could support several new species designations. In fact, prior investigators have proposed the assignment of new species based on isolated case reports or have claimed a greater accuracy of identification with sequencing of the 16S rRNA, rnpB, rpoB, sodA, and/or 16S-23S rRNA spacer targets (1,3,4,6,13,14). We have shown that both phenotype and hierarchy-of-sequence data are often discordant, and the relative ability of a particular DNA target to draw finer phylogenetic distinctions does not necessarily warrant the description of a new species or support greater accuracy of identification.…”
Section: Parasanguinis)mentioning
confidence: 99%
“…By the current and published standard, our unusual sequence variants could support several new species designations. In fact, prior investigators have proposed the assignment of new species based on isolated case reports or have claimed a greater accuracy of identification with sequencing of the 16S rRNA, rnpB, rpoB, sodA, and/or 16S-23S rRNA spacer targets (1,3,4,6,13,14). We have shown that both phenotype and hierarchy-of-sequence data are often discordant, and the relative ability of a particular DNA target to draw finer phylogenetic distinctions does not necessarily warrant the description of a new species or support greater accuracy of identification.…”
Section: Parasanguinis)mentioning
confidence: 99%
“…When there is a low availability of iron, certain bacterial species can achieve an ecological advantage [23]. Interestingly, Streptococci are bacteria that can grow under limited iron conditions [24], which may explain the caries experience in children with reduced salivary iron levels. Another hypothesis is that the lower availability of salivary iron does not inhibit the activity of the glycosyltransferase enzyme, which is responsible for producing insoluble extracellular polysaccharides that in turn confer an ecological advantage to cariogenic bacteria [25].…”
Section: Discussionmentioning
confidence: 99%
“…This relatively high sequence demarcation of 1.3 % strongly suggested the recognition of a novel streptococcal species and an erroneous assignment of strain ATCC 15914, which was typed in 1977 based solely on phenotypic characteristics (Facklam, 1977). Moreover, the correct species assignment of strain ATCC 15914 was questioned recently by several reports on the basis of analyses of the housekeeping genes zwf and gki (Kiratisin et al, 2005) and the 16S-23S rRNA intergenic spacer region (Tung et al, 2006(Tung et al, , 2007. A retrospective analysis of our molecular database revealed three additional clinical streptococcal isolates (AZ_4a, AZ_7a, AZ_10) that displayed the closest 16S rRNA gene sequence similarity to strain ATCC 15914 in the public database.…”
mentioning
confidence: 99%